Perlindungan Hak Waris Anak Yatim Dalam Perspektif Hifz al-Mal Terhadap Sengketa Kewarisan Dengan Kerabat (Asabah) - Muhammad Maksum Ali (MASADIR: Jurnal Hukum Islam, 2026)
This study examines the protection of inheritance rights of orphaned children within Islamic inheritance law through the perspective of hifz al-m?l as a key principle of maq??id al-syar?‘ah. Inheritance disputes frequently arise in practice despite clear legal provisions, often resulting in injustice toward vulnerable parties. Orphaned children are among the most disadvantaged, even though they hold a primary legal status as heirs due to their direct lineage (nasab). However, their limited legal capacity and social vulnerability often expose them to marginalization and exploitation, particularly in disputes involving extended relatives categorized as ‘asabah. This research employs a normative juridical approach through library research, utilizing primary sources such as the Qur’an, Hadith, and the Compilation of Islamic Law, as well as relevant scholarly literature. The findings indicate that orphaned children occupy a prioritized and legally protected position as heirs that cannot be overridden by other relatives whose rights are conditional. Nevertheless, their inability to manage property independently necessitates the implementation of guardianship (wil?yah) as a mechanism to safeguard and administer their inheritance. From the perspective of hifz al-m?l, protection extends beyond preserving assets to ensuring lawful ownership, fair distribution, and preventing unjust appropriation. The study concludes that safeguarding the inheritance rights of orphaned children represents a realization of hifz al-m?l, where inheritance law functions not only as a system of distribution but also as an instrument of justice that protects vulnerable members within the family structure.